Transcriptomic Analysis of Long Non-coding RNA-MicroRNA-mRNA Interactions in the Nucleus Accumbens Related to Morphine Addiction in Mice - Li, Xiaojie; Xie, Bing; Lu, Yun; Yang, Hongyu; Wang, Jian; Yu, Feng; Zhang, Ludi; Cong, Bin; Wen, Di; Ma, Chunling (Frontiers in Psychiatry, 2022)
Recent research suggest that some noncoding RNAs (ncRNAs) are important regulators of chromatin dynamics and gene expression in nervous system development and neurological diseases. Nevertheless, the molecular mechanisms of long noncoding RNAs (lncRNAs), acting as competing endogenous RNAs (ceRNAs), underlying morphine addiction are still unknown. In this research, RNA sequencing (RNA-seq) was used to examine the expression profiles of lncRNAs, miRNAs and mRNAs on the nucleus accumbens (NAc) tissues of mice trained with morphine or saline conditioned place preference (CPP), with differential expression of 31 lncRNAs, 393 miRNAs and 371 mRNAs found. A ceRNA network was established for reciprocal interactions for 9 differentially expressed lncRNAs (DElncRNAs), 10 differentially expressed miRNAs (DEmiRNAs) and 12 differentially expressed mRNAs (DEmRNAs) based on predicted miRNAs shared by lncRNAs and mRNAs. KEGG pathway enrichment analyses were conducted to explore the potential functions of DEmRNAs interacting with lncRNAs in the ceRNA network. These DEmRNAs were enriched in synaptic plasticity-related pathways, including pyrimidine metabolism, ECM−receptor interaction, and focal adhesion. The correlation between the relative expression of lncRNAs, miRNAs and mRNAs was analyzed to further validate predicted ceRNA networks, and the lnc15qD3-miR-139-3p-Lrp2 ceRNA regulatory interaction was determined. These results suggest that the comprehensive network represents a novel avenue for accurately describing the molecular mechanisms of morphine addiction and provides new potential diagnostic and prognostic biomarkers for morphine addiction.